Dinamika Pola Komunikasi Keluarga dalam Pemberian Nafkah: Studi Khuruj Jamaah Tabligh - Ismail, Muhammad; Nurhikmah; A. Nurkidam (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2025)
This study aims to identify the dynamics of family communication patterns in providing sustenance during the implementation of khuruj by members of Jamaah Tabligh at the Al-Ittihad Labatu Mosque, Labukkang Village, Ujung District, Parepare City. This study also examines the impact of khuruj on the provision of sustenance, both physically and mentally, and how family communication patterns are maintained despite physical separation. A qualitative approach with a descriptive case study design was used in this study. Data were collected through in-depth interviews and participatory observations of Jamaah Tabligh family members involved in khuruj. The findings of the study indicate that family communication, which includes deliberation and communication based on religious values, plays a significant role in maintaining household harmony even though the husband leaves the family for a certain period of time. The provision of sustenance that is material and emotional shows that despite limited communication, religious values ​​and understanding between family members can maintain relationship stability and reduce the potential for conflict. This study is expected to provide practical guidance for the Jamaah Tabligh community in managing family communication during khuruj.